HUBUNGAN JARAK KEHAMILAN DENGAN TEKANAN DARAH IBU HAMIL PREEKLAMPSIA - Diki Retno Yuliani; Puji Hastuti (POLTEKKES KEMENKES SEMARANG, 2019)
Relationship Of Inter-pregnancy Interval With Blood Pressure Of Preeclampsia Pregnant Woman : inter-pregnancy interval is a risk factor for preeclampsia, and an increase in blood pressure is a sign of preeclampsia. The purpose of this study was to determine the relationship between inter-pregnancy interval and blood pressure. The study design was a cross sectional analytic survey research. The population was preeclampsia pregnant women in Banyumas District with cluster sampling technique. The results of the study were a relationship between inter-pregnancy interval with systolic blood pressure (p 0.017) and no relationship between inter-pregnancy interval with diastolic blood pressure (p 0.629). The conclusion of this study, there was a relationship between inter-pregnancy interval with systolic blood pressure in preeclampsia pregnant women.